Characterization of Cough Sounds Based on Measured Sound Pressure Levels from Arduino-Based MAX9814 Sound Sensor: Aris widodo, Muktamar Cholifah Aisiyah - Aris Widodo Aris Widodo; Muktamar Cholifah Aisiyah Muktamar Cholifah Aisiyah (Jurnal Fisika dan Aplikasinya, 2023)
Research has been conducted on the characterization of coughing sounds based on the measured sound pressure level of the Arduino-based MAX9814 sound sensor to determine the characteristics of coughing sounds based on the Sound Pressure Level (SPL). This research method is carried out by designing sound sensor hardware and software using the MAX9814 sound sensor. After that, recording the coughing sound data from the cough voice coswara respondent data set using a sound sensor and converting it to SPL data. After that, the cough SPL data was analyzed from the SPL cycle graph during recording and the cough phase pattern. And the resulting characterization of coughing sound based on coughing pressure using an Arduino-based MAX9814 sound sensor produced a coughing sound character in terms of sound pressure level (SPL) based on the expulsive phase and the intermediate phase of coughing. The expulsive phase indicator is emphasized the intensity of occurrence and density in one cycle of recording coughing sounds. And for the intermediate phase based on the drop rate of the SPL back to the SPL position without coughing. The SPL of cough detected by the MAX9814 sound sensor is ±80dB.